Xanthogranuloma is not always yellow. - Ingravallo, G.; Valentini, D.; Bonifazi, E.; Lastilla, G. (European Journal of Pediatric Dermatology, 2006)
A 2 6/12-year-old girl presented for 6 months dermohypodermic nodules. Hospitalized in another Department, she had already performed laboratory examinations and abdomen ultrasonography resulted within normal limits. A biopsy from a nodule of the back, the scar of which was still evident had received a diagnosis of xanthogranuloma. Her nodules were randomly arranged, but prevailing on the back and upper limbs, 1-3 cm in size, covered by normal skin, hard-elastic and movable on the superficial and deep layers. Other organs, laboratory and ophthalmologic examinations were normal. Skeptical about the diagnosis of xanthogranuloma due to the lack of xanthomization, although the disorder had started 6 months before, we removed a nodule. In the deep dermis and fat tissue there was an infiltrate of multivacuolated , CD68+, non Touton giant cells, lymphocytes, eosinophils and plasma cells. The final diagnosis was deep dermohypodermic xanthogranuloma with multiple nodules.